Local Land Subsidence Analysisi In Penang Island (Malaysia) Based On Insar Maps - Gao, Guosheng (2021)
Penang Island is an important economic centre in Malaysia that has experienced land subsidence in recent years. In this study, the PS-InSAR and SBAS-InSAR techniques are used to monitor land subsidence of Penang Island based on Sentinel-1 SAR radar images in both ascending and descending tracks.